ANALISIS USHUL DAN KAIDAH FIKIH TERHADAP IMPLEMENTASI DISPENSASI PERKAWINAN DI BAWAH UMUR DI KANTOR URUSAN AGAMA (KUA) KECAMATAN PERAK KABUPATEN JOMBANG - Arofik, Slamet; Riski Yustomi, Alvian (USRATUNA: Jurnal Hukum Keluarga Islam, 2020)
an be justified and valid according to the applicable law. Likewise, if it is analyzed using the theory of establishing Islamic law, namely the disciplines of Ushul Fikih and the Law of Fikih, the policies that have been adopted by the KUA of Perak sub-district of Jombang district are in accordance with the Fikih Principles and the Maslahah Mursalah theory in the study of Ushul Fiqh.